Altered Gut Microbiota and Shift in Bacteroidetes between Young Obese and Normal-Weight Korean Children: A Cross-Sectional Observational Study. (18th August 2020) - Shin, Saeam; Cho, Ky Young
Abstract : Emerging data suggest that the gut microbiome is related to the pathophysiology of obesity. This study is aimed at characterizing the gut microbiota composition between obese and normal-weight Korean children aged 5-13. We collected fecal samples from 22 obese and 24 normal-weight children and performed 16S rRNA gene sequencing using the Illumina MiSeq platform. The relative abundance of the phylum Bacteroidetes was lower in the obese group than in the normal-weight group and showed a significant negative correlation with BMI z -score. Linear discriminative analysis (LDA) coupled with effect size measurement (LEfSe) analysis also revealed that the Bacteroidetes population drove the divergence between the groups. There was no difference in alpha diversity, but beta diversity was significantly different between the normal-weight and obese groups. The gut microbial community was linked to BMI z -score; blood biomarkers associated with inflammation and metabolic syndrome; and dietary intakes of niacin, sodium, vitamin B6, and fat. The gut microbiota of the obese group showed more clustering of genera than that of the normal-weight group. Phylogenetic investigation of communities by reconstruction of unobserved states (PICRUSt) analysis revealed that the functions related to carbohydrate and lipid metabolism in the microbiota were more enriched in the normal-weight group than in the obese group. Our data may contribute to the understanding of the gut microbial structure of young Korean children in relation to obesity. These findings suggest that Bacteroidetes may be a potential therapeutic target in pediatric obesity.